Impact of geometries on performances and surface morphology of SLS 3D-printed thrust and roller bearings - Abdullah, Muhammad Ilman Hakimi Chua; Alkahari, Mohd Rizal; Abdollah, Mohd Fadzli; Mohamad Fazdhli, Fawzan Hanafi; Wei, Ignatius Wong Loke; Abdul Khalid, Alif Iqmal; Abdullah, Rohana; Muhamad Damanhuri, Amir Abdullah; Mohamad, Effendi; Puspitasari, Poppy (Accent Social and Welfare Society, 2025)
Bearings are among the most prevalent elements in civil engineering buildings and mechanical machinery, with numerous applications. The global bearings market has experienced considerable growth in recent years, fuelled by rising demand in the automotive, aerospace, and manufacturing sectors. Bearings were used as early as 40 Before Christ (BC) and commonly have a solid geometrical design. Lately, there have been limited studies to predict the effects of different geometries on the behaviour of bearings. In this study, different geometrical models were designed using CatiaV5 software and manufactured using selective laser sintering (SLS) three-dimensional (3D) printing. The printed geometrical bearing samples were subjected to vibration analysis, performance testing, and surface validation using a scanning electron microscope (SEM) to evaluate their tribological behaviour. The findings indicated that the samples with a triangular geometry exhibited a remarkably smooth surface texture. This smoothness surpassed that of the samples with a square geometry, and this was attributed to the shorter spacing between the melted particles, extensive coverage of the particle area and reduced presence of independent particles. These findings highlight the intricate interplay between geometry and surface texture in bearing fabrication, offering valuable insights for further research and development.